Marketing strategy development and market segmentation analysis of PT. Wijaya Karya on government policies in the building EPC champion program - Arga Bima; Atik Aprianingsih (Jurnal Perilaku dan Strategi Bisnis, 2022)
The Indonesian government's efforts to synergize state-owned enterprises continue to be intensifying. The Ministry of State-Owned Enterprises continues to streamline and improve the portfolio of the number of SOEs through corporate restructuring with a holding system, mergers, and acquisitions. As an initial step towards creating an infrastructure SOES holding, the Ministry of SOES launched a "Building EPC Champion" program which aims to regroup companies in the EPC sector based on their business strengths to become market segment leaders. Through the program of the Ministry of SOEs, PT. Wijaya Karya (Persero) Tbk will become the industrial sector market segment champion, including the Industrial and Metals and Mining markets. By referring to the company's historical financial data, and its operational performance, there must be an evaluation of WIKA's ability to become a champion in the industrial sector. The object of research in this final project is the condition of the industrial market. This final project research uses internal and external environmental analysis to find company business solutions. The internal analysis uses Resource Analysis, Capabilities Analysis, and Value Chain Analysis. Meanwhile, the external analysis uses PESTEL analysis, Porter's Five Forces Analysis, Market Analysis, Competitor Analysis, and Consumer Analysis. Analysis of IFE and EFE Matrix was carried out to analyze the company's Strengths, Weaknesses, Opportunities, and Threats and through TOWS Analysis to obtain the development of marketing strategies from this research. The IE Matrix and the QSPM Matrix assessment show that carrying out a cooperation strategy with competent foreign companies can increase the company's capabilities and competencies as capital to compete in the Indonesian industrial market. Keywords – Engineering, Procurement, Construction, Industrial, Marketing